Acral pseudolymphomatous angiokeratoma of children (APACHE)‐like eruption in adult identical twins. (1st October 2016) - Fonia, A.; Bhatt, N.; Robson, A.; Kennedy, C. T. C.
Summary: Acral pseudolymphomatous angiokeratoma of children (APACHE) is a condition that was first described in 1990 in a group of children, but has since been described in adults. We present the cases of identical twin patients aged 40 years. The first brother presented with an 8‐year history of itchy lesions over the left ankle and the insteps of both feet. After a diagnostic biopsy, he was treated with potent steroids under occlusion for 8 weeks, which resulted in flattening of the lesions and resolution of the pruritus. The second twin had a 20‐year history of a very similar presentation but the lesions were less pronounced; he chose not to have treatment. No other family members were affected. Skin biopsies from both patients showed similar changes. Within an overall hyperkeratotic and acanthotic epidermis, there were focal areas of lichenoid change and epidermal thinning. Beneath these areas, there was oedema and nodular aggregates of dense inflammatory cell infiltrate, predominantly lymphocytic infiltrate. APACHE has not been previously described in twins.